ONOMATOPE DALAM KOMIK MILES MORALES: SPIDER-MAN 2019 - Lingga Julinafta; Retno Purwani Sari (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2022)
The study investigates onomatopoeia in all of its forms and meanings as seen in the digital comic "Miles Morales: Spider-Man 2019" by Saladin Ahmed on the website https://readcomicsfree.com. It employed Sperber and Wilson's relevance theory (1986) to describe meanings in digital comics through a descriptive qualitative approach based on the interdependence of onomatopoeia and imagery. The theories of Wijana (2008) and Thomas and Clara (2004) were used to categorize the types of onomatopoeia. Data was gathered using episode 1 page 9-23 and episode 20 page 14. The findings indicate a link between onomatopoeia and imagery in determining communicated meanings. Onomatopoeia can be monosilable, bisilable, or multisilable in terms of morphology. It is recognized for its ability to mimic human and animal sounds, as well as other sounds. The narrative messages of digital comics can be fully comprehended using these concepts. Keywords: Digital Comic. Mimetics, Onomatopoeia, Relevance Theory, Sound Mimetic